’Salimu’: from Memory to Literary Narrative in Twentieth-Century manding Culture - Tamari, Tai (Afrika Focus, 2019)
This essay explores the creation of new literary narratives, many inspired by true incidents, from the late nineteenth century to the present, among Manding- (specifically Maninka-) speakers in Mali and Guinea. It simultaneously queries the relationships between Manding and Western literary categories, showing that the traits typically associated with African ‘epics’ – including poetic language, alternation of sung and recited passages to continuous instrumental accompaniment, and multi-generic qualities – characterise some (but not all) examples of several distinct Manding literary categories (fasa, tariku and maana); furthermore, these traits appear in narratives of various lengths, centred on sentimental as well as heroic themes. It then focuses on the stories and songs inspired by the apparently contradictory personality of Salimou Haidara (ca. 1930-1991), an eccentric who claimed sharifian descent. A performance by Amadou Kouyaté and Jekoriya Doumbia, a bard couple based in the village of Dabadou near Kankan (Guinea), is transcribed, translated, and analysed1. KEYWORDS: EPIC, LITERARY GENRE, GRIOTS, MANINKA, KANKAN (GUINEA), CHEIKH MOUHAMMAD CHÉRIF